Competitive Advantage Strategy Development at SDIT At Taqwa Surabaya - Hasanah, Ula Mauidhotul; Roesminingsih, Erny; Mudjito, Mudjito (International Journal for Educational and Vocational Studies, 2021)
This study aims to produce a competitive advantage strategy product at the Integrated Islamic Elementary School of At Taqwa Surabaya by looking at the feasibility, practicality and effectiveness of the strategy. The approach and type of research used is development research with a descriptive quantitative approach. The data obtained in this research and development comes from the results of interviews, observations, documentation, and questionnaires filled out by expert validators and subjects who have been selected into a small group involved in the study. Data analysis was carried out by: (1) validity data analysis, (2) practicality data analysis, (3) effectiveness data analysis. This research and development resulted in a product in the form of compiling a model for developing a competitive advantage strategy at SDIT At Taqwa Surabaya that was valid, practical, and effective. The product consists of several components which include: (1) title page, (2) introduction, (3) introduction, (4) steps for implementing a competitive advantage strategy development model that must be carried out by the Principal, Deputy Principal, Field Coordinator , and Homeroom Teacher. The feasibility of the product in the form of compiling a competitive advantage strategy development model at SDIT At Taqwa Surabaya obtained the following values: (1) validity of 3.3 from a maximum value of 4, (2) practicality of 2.87 from a maximum value of 4, and (3) effectiveness of 2.71 of the maximum value of 4.